Preoperative Assessment Proposal - Macedo Peña, Víctor (2000)
OBJECTIVES: To design two different surgical patient groups with nonsimilar surgical risks one of them in normal range an the other in high risk. MATERIALS AND METHODS: Two groups of patients of a hundred cases each were evaluated. The first group of healthy kidney donors underwent unilateral nephrectomy, were thoroughly studied in accordance to a preestablished protocol. This protocol was analyzed and we established twelve types of surgical risks, having a risk scale that ranges from I to IV. In the second group of patients who underwent high risk major abdominal surgery we established a scoring method that allows us to determine the patient prognosis. RESULTS: The study demostrated differences in the preoperative assessments.In the fisrt group 99,75% of patients presented risk I, in the other group more than 40 % presented risk II to IV. The morbimortality had a significative difference: 1 % in donors and 19% in the ones of major surgery. Only in the second group there was 4% of mortality. CONCLUSIONS: Group I patients had excellent course, high risk patients had high morbi-mortality, the here proposed preoperative assessment must be used in high risk patients since it allows us to establish the patient prognosis.